Decreased serum C1Q/TNF-related protein 4 concentrations are associated with type 2 diabetes mellitus. (November 2021) - Liu, Zheng; Lu, Jinhua; Zhang, Daiyi; Niu, Lijuan; Shi, Bimin
Objective: To detect serum C1Q/TNF-related protein 4 (CTRP4) concentrations in patients with newly diagnosed type 2 diabetes mellitus (T2DM) and evaluate the correlation between CTRP4 and other variables in T2DM. Method: Sixty-five patients with newly diagnosed T2DM and eighty-nine healthy volunteers were enrolled in this study. Anthropometric and biochemical data of the study participants was collected, and serum CTRP4 concentrations were detected by enzyme-linked immunosorbent assay (ELISA) kit. The correlation between serum CTRP4 and other indexes was analyzed by Spearman correlation analysis. Trend χ 2 test and binary multivariate stepwise logistic regression were performed to assess the correlation between CTRP4 and the risk of T2DM. Results: Serum CTRP4 concentrations in the T2DM group were significantly lower than those in the control group ( P < .01). Spearman correlation analysis showed that CTRP4 concentrations were negatively correlated with BMI, hs-CRP, HOMA-IR, FBG and TG ( r = - 0.430, - 0.453, - 0.371, - 0.361, - 0.506, P < .05), and positively correlated with HDL-c ( r = 0.303, P < .05). Trend χ 2 test indicated that with the increase of CTRP4 levels in the population, the risk of T2DM presented a general downward trend ( P < .01). Binary multivariate stepwise logistic regression suggested that serum CTRP4 was an independent impact factor for T2DM and high serum CTRP4 levels were related to the decreased risk of T2DM (P < .05). Conclusions: Serum CTRP4 concentrations decrease in patients with newly diagnosed T2DM. Serum CTRP4 levels are negatively associated with the risk of T2DM.